If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = -11 + -2x Reorder the terms: 9 + 2x = -11 + -2x Solving 9 + 2x = -11 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 2x + 2x = -11 + -2x + 2x Combine like terms: 2x + 2x = 4x 9 + 4x = -11 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 4x = -11 + 0 9 + 4x = -11 Add '-9' to each side of the equation. 9 + -9 + 4x = -11 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = -11 + -9 4x = -11 + -9 Combine like terms: -11 + -9 = -20 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| 3x+45.87= | | 2+3x=-8+x | | lnx+ln(x+7)=1 | | 2z+12=36 | | 10x-y=53 | | 14x+2y=8 | | 2x^3+21x+17x^2=0 | | 5x+3y^2=12 | | 56a+43=32a | | e+r=s | | 3x^2+6x+4=12 | | r=ht | | 81k^2+-1=8 | | 9(9-8x-4x)+8(3x+4)=11 | | r+m=b | | x^3-61=3 | | -4x^2+8x+11=0 | | 12t^2=27+27t | | .5x^2+2x-30=0 | | 10w^2-200=0 | | 8x+-2=6x | | 8x-2=6x | | w^2+11w-200=0 | | lnx=-4.833559 | | (8b^4-b^3)-(b^4+4b^3-4)= | | 4x^4+2x^3-108x-54=0 | | y^2+8x+16=0 | | x^3-9*x-1=0 | | y^2+6x+14y+43=0 | | 2y^2+14y+43=0 | | -16x^2+64x+128=0 | | -16x^2+64x+28=0 |